CRISPR/Cas9‐mediated knockout of six glycosyltransferase genes in Nicotiana benthamiana for the production of recombinant proteins lacking β‐1, 2‐xylose and core α‐1, 3‐fucose. Issue 2 (11th August 2018) - Jansing, Julia; Sack, Markus; Augustine, Sruthy Maria; Fischer, Rainer; Bortesi, Luisa
Summary: Plants offer fast, flexible and easily scalable alternative platforms for the production of pharmaceutical proteins, but differences between plant and mammalian N‐linked glycans, including the presence of β‐1, 2‐xylose and core α‐1, 3‐fucose residues in plants, can affect the activity, potency and immunogenicity of plant‐derived proteins. Nicotiana benthamiana is widely used for the transient expression of recombinant proteins so it is desirable to modify the endogenous N‐glycosylation machinery to allow the synthesis of complex N‐glycans lacking β‐1, 2‐xylose and core α‐1, 3‐fucose. Here, we used multiplex CRISPR/Cas9 genome editing to generate N. benthamiana production lines deficient in plant‐specific α‐1, 3‐fucosyltransferase and β‐1, 2‐xylosyltransferase activity, reflecting the mutation of six different genes. We confirmed the functional gene knockouts by Sanger sequencing and mass spectrometry‐based N‐glycan analysis of endogenous proteins and the recombinant monoclonal antibody 2G12. Furthermore, we compared the CD64‐binding affinity of 2G12 glycovariants produced in wild‐type N. benthamiana, the newly generated FX‐KO line, and Chinese hamster ovary (CHO) cells, confirming that the glyco‐engineered antibody performed as well as its CHO‐produced counterpart.